2014
DOI: 10.1128/aem.01434-14
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Biofilm Formation by T7 Bacteriophages Producing Quorum-Quenching Enzymes

Abstract: Bacterial growth in biofilms is the major cause of recalcitrant biofouling in industrial processes and of persistent infections in clinical settings. The use of bacteriophage treatment to lyse bacteria in biofilms has attracted growing interest. In particular, many natural or engineered phages produce depolymerases to degrade polysaccharides in the biofilm matrix and allow access to host bacteria. However, the phage-produced depolymerases are highly specific for only the host-derived polysaccharides and may ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
102
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(109 citation statements)
references
References 52 publications
(85 reference statements)
6
102
0
1
Order By: Relevance
“…A thicker biofilm results. This is in accordance with a previous finding (36) that mucoid phage-resistant E. coli colonies appeared when a preformed biofilm was treated with phage T7 for 1 h. There is another report describing the successful suppression of E. coli biofilms by T7 infection (37). However, the authors did not observe biofilm formation long enough for the encapsulated mutants to become dominant; thus, they claimed that T7 was effective at inhibiting biofilm formation.…”
Section: Discussionsupporting
confidence: 73%
“…A thicker biofilm results. This is in accordance with a previous finding (36) that mucoid phage-resistant E. coli colonies appeared when a preformed biofilm was treated with phage T7 for 1 h. There is another report describing the successful suppression of E. coli biofilms by T7 infection (37). However, the authors did not observe biofilm formation long enough for the encapsulated mutants to become dominant; thus, they claimed that T7 was effective at inhibiting biofilm formation.…”
Section: Discussionsupporting
confidence: 73%
“…Other studies have demonstrated T7 engineered phage expressing the EPS-degrading enzyme Dispersin B to be more efficient in killing E. coli biofilms than phages alone (46). A recent study utilizing a phage expressing a lactonase enzyme that degrades quorum sensing bacterial signaling molecules was shown to be effective in preventing biofilm formation in mixed cultures of P. aeruginosa and E. coli (47).…”
Section: Bacteriophage Therapy To Fight Biofilm Infectionsmentioning
confidence: 99%
“…The key intent behind this strategy is not to kill pathogens but to disarm them making them oversensitive to the normal antimicrobial treatments. Furthermore, the QS system is not contributing in any way in mechanisms which can be essential for the bacteria survival, but inhibiting this method won't be described as a reason behind producing a firm selective pressure suitable enough to cause resistance development [53,54]; showed that the engineered phage strain T7 that creates the metalloenzymes AiiA lactonase range of action against signalling molecules (acyl homoserine lactones) which are mixed up in bacterial quorum sensing is extremely wide that is and these molecules are important for the development of the biofilm.…”
Section: Quorum Sensing Inhibition (Qsi) By Phagesmentioning
confidence: 99%